Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kepuasan Karyawan Di PT. Asuransi Ramayana Kota Malang - Handik Purwantoro; Arzak Permana Susanto (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2024)
ABSTRACTHR is something that is very important and must be owned in order to achieve organizational or company goals.  HR is the main element of an organization that functions to implement management functions, namely planning, organizing, leading and controlling so that company goals can be achieved.  This research aims to determine the influence of Leadership Style and Compensation on Employee Performance at PT Asuransi Ramayana Malang Branch. The population of this research was 39 employees of PT Asuransi Ramayana Malang Branch with the sample size selected being all employees. In this research, the sampling technique used by the author is the Non Probability Sampling technique using the saturated sampling method. Saturated sampling is a sampling method when all members of the population are used as samples. . In this research, researchers will take all 39 employees at PT Asuransi Ramayana Malang Branch to be used as samples. The data collection method in this research is the questionnaire method. The data analysis technique used is multiple linear regression analysis. The results of this research show that 1. Leadership style variables have a positive and significant effect on employee performance at PT. Ramayana Insurance Malang Branch. 2. The compensation variable has no effect on employee performance at PT. Ramayana Insurance Malang Branch. Keywords: Compensation, Leadership Style and Employee Performance.